1992
DOI: 10.1159/000147314
|View full text |Cite
|
Sign up to set email alerts
|

Fine Structure of the Dorsal Lingual Epithelium of the Japanese Monkey Macaca fuscata fuscata

Abstract: Filiform papillae, which were densely distributed all over the dorsal surface of the lingual body, were crown-shaped, with a central, circular area that sloped in the anterior direction and several branches that surrounded it in a semicircle from the back of the central area. Dome-shaped, fungiform papillae were scattered among these filiform papillae. At the posterior end of the lingual body, there were four circumvallate papillae. Prominent microridges and elevated intercellular borders were widely distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

1995
1995
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In this case, however, the dorsal lingual epithelium of the sea turtle is composed of stratified squamous cells, which are more protective of the inside of this organ than are stratified cuboidal cells. In fact, the composition of the lingual epithelium of the sea turtle is very similar to that of terrestrial vertebrates, irrespective of whether or not lingual papillae are present (Cane and Spearman, 1969;Farbman, 1970;Hume and Potten, 1976;Miyata, 1989, 1990;Iwasaki, 1992b;Iwasaki et al, 1992b). Further observations in numerous species are necessary to confirm the validity of our hypothesis.…”
Section: Discussionsupporting
confidence: 52%
“…In this case, however, the dorsal lingual epithelium of the sea turtle is composed of stratified squamous cells, which are more protective of the inside of this organ than are stratified cuboidal cells. In fact, the composition of the lingual epithelium of the sea turtle is very similar to that of terrestrial vertebrates, irrespective of whether or not lingual papillae are present (Cane and Spearman, 1969;Farbman, 1970;Hume and Potten, 1976;Miyata, 1989, 1990;Iwasaki, 1992b;Iwasaki et al, 1992b). Further observations in numerous species are necessary to confirm the validity of our hypothesis.…”
Section: Discussionsupporting
confidence: 52%
“…The fine structure of lingual epithelia has been studied in various species of animals (KATO and KUSHIDA, 1965;KUBOTA et al, 1966;FARBMAN, 1970;CANE and SPEARMAN, 1969;GREENBAUM and PHILLIPS, 1974;HUMS and POTTEN, 1976;FERNANDEZ et al, 1978;SINGH et al, 1980;BOSHELL et al, 1980aBOSHELL et al, , b, 1982HOFER,1981;KRAUSE and CUTTS, 1982;STERFLICK et al, 1983;MACKENZIE and BICKENBACH, 1984;MACK-ENZIE and DABELSTEEN, 1987;OHMURA, 1988;KONDO et al, 1988;IWASAKI andMIYATA, 1989, 1990;IWASA-KI, 1990, IWASAKI et al, 1992. These studies demonstrated that lingual epithelia vary to a considerable extent in morphology among different species, showing unique external configurations represented by the presence of various types of papillae.…”
Section: Discussionmentioning
confidence: 99%
“…Shapes and structures of filiform papillae vary among different species, and it is speculated that such differences in the morphologies of filiform papillae may reflect thier phylogeny to some extent (IWASAKI et al, 1992). Although some studies reported that epithelia of filiform papillae in several kinds of mammals are not morphologically divisible into anterior and posterior areas (BOSHELL et al, 1982;STER-FLICK et al, 1983;IWASAKI and MIYATA, 1990), this study clearly demonstrates that human dorsal lingual epithelia show three distinct regions, i. e., epithelia on the anterior and on the posterior sides and the interpapillary epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations